The Role of the Political Elite in the Development of Society A theoretical Study in the Kurdistan Region - Twana Othman Mohamedamen (Zanco Journal of Humanity Sciences)
The study of the elite occupies great importance in the field of political sociology topics, this is because the elite possesses the influential tools for formation and stability of societies and formation of rolling the system and notion and believe orientation...etc. With no doubt of that, the political elites in human societies play a prominent role in the processes of change towards social development,  in all social forms. And will take high responsibility for leading society or retreatment and therefore it can be considered as the most prominent and the important contributor in social development that required the elite to be in a high level of responsibility to lead the society to what its members aspire to in terms of improving their living conditions and raising the efficiency of work and production. The strategic role of the elites is embodied in making public opinion and directing it in a number of aspects and leading the process. This research consists of an introduction, three chapters, and a conclusion, and each chapter includes a number of topics. In the first chapter, which is titled Dimensions of the Study and Defining Concepts, the first topic problem and the importance of the research were defined, and also its objectives. In the second topic, the main terminology such as the elite, the political elite, and social development was discussed. In the second chapter the search for ideological direction, quality, and the elite theories, this is through three topics, the first explaining the intellectual trend about the elite and the political elite, and the second topic deals with the issue of different types of elites in the society, and the third topic is devoted to clarifying the elite theories. As for the third and final chapter, specified to clarify the relationship between the elite and social development through two topics, the first to explain the role and influence of the political elite in the process of social development, and the second topic to clarify the political elite in Kurdish society. Finally, the research reached a set of results. The political elite has the most prominent role in the process of social development during its role in state institutions and outside it within the framework of society, as this elite is the main engine for the functioning of the political system and the movement of the various political forces within the society.